2023
DOI: 10.1146/annurev-biodatasci-020222-021705
|View full text |Cite
|
Sign up to set email alerts
|

Human Genomics of COVID-19 Pneumonia: Contributions of Rare and Common Variants

Abstract: SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) infection is silent or benign in most infected individuals, but causes hypoxemic COVID-19 pneumonia in about 10% of cases. We review studies of the human genetics of life-threatening COVID-19 pneumonia, focusing on both rare and common variants. Large-scale genome-wide association studies have identified more than 20 common loci robustly associated with COVID-19 pneumonia with modest effect sizes, some implicating genes expressed in the lungs or leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 162 publications
0
6
0
Order By: Relevance
“…Rare and common human genetic variants have been associated with hypoxemic COVID-19 pneumonia. 1 , 2 , 3 , 4 , 5 , 6 Inborn errors of TLR3- and/or TLR7-dependent type I interferon (IFN) immunity underlie critical COVID-19 pneumonia in 1%–5% of cases. 1 , 7 , 8 , 9 Moreover, autoantibodies neutralizing type I IFN underlie at least another 15% of cases, 10 , 11 , 12 further highlighting the key role of type I IFNs in protective immunity to SARS-CoV-2 infection in the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…Rare and common human genetic variants have been associated with hypoxemic COVID-19 pneumonia. 1 , 2 , 3 , 4 , 5 , 6 Inborn errors of TLR3- and/or TLR7-dependent type I interferon (IFN) immunity underlie critical COVID-19 pneumonia in 1%–5% of cases. 1 , 7 , 8 , 9 Moreover, autoantibodies neutralizing type I IFN underlie at least another 15% of cases, 10 , 11 , 12 further highlighting the key role of type I IFNs in protective immunity to SARS-CoV-2 infection in the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…Primary infection with SARS-CoV-2 underlies a broad spectrum of clinical manifestations in unvaccinated individuals, ranging from silent infection to lethal COVID-19 pneumonia. Rare and common human genetic variants have been associated with hypoxemic COVID-19 pneumonia [1][2][3][4][5] . Inborn errors of TLR3-and/or TLR7-dependent type I IFN immunity in respiratory epithelial cells and plasmacytoid dendritic cells underlie critical COVID-19 pneumonia in 1-5% of cases 1,[6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Some of them have provided compelling evidence about the importance of genetic variants in the disease, which has helped to better understand the mechanisms of the disease. However, the impact and prevalence of rare and common variants in genes important in the COVID-19 response can change due to the genetic variability of the population studied, implying potentially different risks for each region of the globe ( Kehdy et al, 2015 ; Secolin et al, 2019 ; Zhang et al , 2022a ; Cobat et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the colonization associated with geographic and social processes also favored the formation of isolated populations groups with different genetic characteristics due to geographic isolation, endogamy, size, and effectiveness of the reduced population, being some of them have a high prevalence of genetic disorders ( Cardoso et al, 2019 ). This complex genetic pattern encompasses both common and rare variants, which can have an impact on several health conditions, including COVID-19 and other infectious diseases ( Cobat et al, 2023 ). Indeed, it has already been observed that isolated populations and private genetic variants of some populations present different impacts depending on the region and infections analyzed ( Bastard et al, 2022a ; Duncan et al, 2022 ; Couto-Silva et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation